Kesadaran Komunitas dalam Membangun Budaya Anti-Bullying di Lingkungan Madrasah - Zakarina, Uznul; Tangkudung, Mutmain; Sudai, Rahmawati; Ananda, Adelia; Patpaylohohi, Agustrianto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Bullying prevention can be done with an anti-bullying policy, the policy can create awareness and make the school environment comfortable, the school is obliged to support every positive activity involving the entire school community. This research aims to understand the extent of community awareness in an effort to build an anti-bullying culture in the madrasah environment. This study uses a qualitative method with observation, interview, and documentation data collection techniques. The results of the study show that most Madrasas have implemented anti-bullying policies and programs involving teachers, students, and parents. However, there are still several bullyings that occur, namely physical, verbal, social and cyberbullying, which have a negative impact on victims.